2017
DOI: 10.1007/s10549-017-4262-0
|View full text |Cite
|
Sign up to set email alerts
|

A breast cancer gene signature for indolent disease

Abstract: PurposeEarly-stage hormone-receptor positive breast cancer is treated with endocrine therapy and the recommended duration of these treatments has increased over time. While endocrine therapy is considered less of a burden to patients compared to chemotherapy, long-term adherence may be low due to potential adverse side effects as well as compliance fatigue. It is of high clinical utility to identify subgroups of breast cancer patients who may have excellent long-term survival without or with limited duration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 14 publications
3
36
0
Order By: Relevance
“…Our results are consistent with previous literature regarding the prognostic value of Ki‐67 in breast cancer patients, and recent studies emphasizing the important role of proliferation in breast cancer prognosis, especially in ER‐positive breast cancer . Recently, an ultralow‐risk classification based on the 70‐gene signature was reported, of which 96% were Ki67‐low and 89% were designated as luminal A . Our results also support that Ki‐67 is an important prognostic parameter in ER‐positive invasive breast cancer, whereas BPE may not provide prognostic information in node‐negative tumors, which generally have a good outcome …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are consistent with previous literature regarding the prognostic value of Ki‐67 in breast cancer patients, and recent studies emphasizing the important role of proliferation in breast cancer prognosis, especially in ER‐positive breast cancer . Recently, an ultralow‐risk classification based on the 70‐gene signature was reported, of which 96% were Ki67‐low and 89% were designated as luminal A . Our results also support that Ki‐67 is an important prognostic parameter in ER‐positive invasive breast cancer, whereas BPE may not provide prognostic information in node‐negative tumors, which generally have a good outcome …”
Section: Discussionsupporting
confidence: 91%
“…[21][22][23][24] Recently, an ultralow-risk classification based on the 70-gene signature was reported, of which 96% were Ki67-low and 89% were designated as luminal A. 25,26 Our results also support that Ki-67 is an important prognostic parameter in ER-positive invasive breast cancer, whereas BPE may not provide prognostic information in node-negative tumors, which generally have a good outcome. 27 Recently, van der Velden reported that contralateral BPE was significantly associated with long-term outcome, particularly in ER-positive, HER2-negative invasive breast cancer patients.…”
Section: Discussionsupporting
confidence: 71%
“…Third, the interviews were conducted in a hospital setting, which could have resulted in a social desirability bias leading to under-reporting of patient and diagnostic delays and over-reporting of desirable behaviour such as self-breast examination. Fourth, it is possible that the long waiting period for some of the cases may reflect indolent breast cancer cases54 or benign breast conditions. Fifth, the study was a hospital-based study, and thus might not capture the experience of women who solely seek care elsewhere (eg, traditional or spiritual healers) or women who are seen only at primary care facilities and do not get to the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Additional data derived from larger untreated (and unselected) patient series to support these results are warranted but difficult to obtain. Delahaye et al recently reported an ultralow/indolent signature based on the 70-gene signature, identifying a small subgroup of patients not receiving adjuvant treatment who had 100% 15 years of BCSS [ 30 ]. Comparison of this ultralow signature with the low-risk ROR score would be of interest.…”
Section: Discussionmentioning
confidence: 99%